Environmental effects of cocaine addiction: the muscle of the European eel (Anguilla anguilla) exposed to environmental cocaine concentrations - GAY, FLAMINIA; Cerulo M; LAFORGIA, VINCENZA; CAPALDO, ANNA (2014)
Objective: Cocaine is a common organic contaminant of the aquatic environment (Pal et al. 2013). Due to its pharmacological activity, its presence in surface waters suggests new hazards, still unknown, for fish, living in contaminated waters. A chronic exposure to environmental cocaine concentrations (20 ng/l) alters the endocrine system of European eels (Gay et al. 2013) that accumulate cocaine into their tissues, especially muscle (Capaldo et al. 2012), the edible part of the animal, suggesting risks for this species and potentially for humans, consuming contaminated fish. Therefore, we aimed to verify whether environmental cocaine concentrations could damage the muscle of the European eel. Method: Adult eels were divided into four groups (control, carrier, treated, post-exposure recovery), each containing ten specimens. A stock solution of 3 mg/500 ml cocaine free-base in ethanol was prepared. Control, treated and carrier groups were exposed daily, during 50 days, to: tap water; 20 ng/l cocaine; ethanol, respectively; a post-exposure recovery group was exposed to cocaine, as treated group, and then deprived of cocaine and exposed to tap water, during ten days. Plasma levels of the following enzymes and hormones were determined: lactate dehydrogenase (LDH) and M1 muscle-specific creatine kinase (M1-CK), well-known indicators of tissue injury; growth hormone- releasing hormone (GHRH) and corticotrophin- releasing hormone (CRH), regulating in the eel growth hormone (GH) release; GH and insulin-like growth factor 1 (IGF-1), involved in eel muscle metabolism. Samples of muscles were fixed in Bouin solution, embedded in Paraplast and stained with Mallory trichromic stain for histological examination. Results: Cocaine significantly (P < 0.001) increased the levels of LDH (from 45.30 U/ml in controls to 62.60 U/ml in treated); M1-CK (from 38.52 U/ml to 151.28 U/ml); GHRH (from 2.15 ng/ml to 7.33 ng/ml); CRH (from 50.13 ng/ml to 82.13 ng/ml); GH (from 0.90 ng/ml to 3.27 ng/ml); IGF-1 (from 0.28 ng/ml to 0.85 ...